Neurodevelopmental outcome of late preterm infants in Johannesburg, South Africa - Tanusha Ramdin; Daynia Ballot; David Rakotsoane; Lethile Madzudzo; Nicolette Brown; Tobias Chirwa; Peter Cooper; Victor Davies (BMC, 2018)
Abstract Background Late preterm infants, previously considered low risk, have been identified to be at risk of developmental problems in infancy and early childhood. There is limited information on the outcome of these infants in low and middle income countries. Methods Bayley scales of infant and toddler development, version III, were done on a group of late preterm infants in Johannesburg, South Africa. The mean composite cognitive, language and motor sub-scales were compared to those obtained from a group of typically developed control infants. Infants were considered to be "at risk" if the composite subscale score was below 85 and "disabled" if the composite subscale score was below 70. Infants identified with cerebral palsy were also reported. Results 56 of 73 (76.7%) late preterm infants enrolled in the study had at least one Bayley assessment at a mean age of 16.5 months (95% CI 15.2-17.6). The mean birth weight was 1.9 kg (95%CI 1.8-2.0) and mean gestational age 33.0 weeks (95% CI 32.56-33.51). There was no difference in the mean cognitive subscales between late preterm infants and controls (95.4 9, 95% CI 91.2-99.5 vs 91.9.95% CI 87.7-96.0). There was similarly no difference in mean language subscales (94.5, 95% CI 91.3-97.7 vs 95.9, 95% CI 92.9-99.0) or motor subscales (96.2, 95% CI 91.8-100.7 vs 97.6, 95% CI 94.7-100.5). There were four late preterm infants who were classified as disabled, two of whom had cerebral palsy. None of the control group was disabled. Conclusions This study demonstrates that overall developmental outcome, as assessed by the Bayley scales of infant and toddler development, was not different between late preterm infants and a group of normal controls. However, 7.1% of the late preterm infants, had evidence of developmental disability. Thus late preterm infants in low and middle income countries require long term follow up to monitor developmental outcome. In a resource limited setting, this may best be achieved by including a parental screening questionnaire, such as the Ages and Stages Questionnaire, in the routine well baby clinic visits.